ECONOMIC ANALYSIS OF PORTLAND CEMENT CONCRETE HIGHWAY PAVEMENT FOR INDONESIA - Harapan Gultom, Antonius
The use of Portland cement concrete (PCC) highway pavement in Indonesia began in the mid-1980s. At the same time, a surplus of domestic Portland cement production was reached. Consequently there is an incentive to increase the use of Portland cement for the construction of highway pavements to absorb the surplus production of Portland cement and to reduce a dependency on imported asphalt. This thesis describes the possibility of applying PCC highway pavement in Indonesia from the viewpoints of availability of materials and the level of demand for Portland cement for road construction. Data on PCC highway pavements that have been constructed in Indonesia are presented. The literature survey, as an integral component of the thesis, includes engineering aspects of PCC highway pavements from various sources. The basis of the economic analysis utilized the life-cycle costing method. Most of the data used in the economic analysis were obtained from references, Puslitbang Jalan-PU, P.T. Jasa Marga, and engineering consultants who had dealt with the designing of PCC pavements. The decision of whether to construct a highway or not is normally based on a full analysis of economy over the life-cycle period of the project. A case study for this thesis is the Panci-Bandung bypass project which will be constructed using PCC pavement. Flexible pavement was proposed as an alternative. For the purpose of economic analysis in the present research, three alternatives were `studied: flexible pavement, machine-intensive construction of PCC pavement, and labour-intensive construction of PCC pavement. In the analysis, the effects of shadow pricing of the material components (Portland cement and the imported asphalt) and the sensitivity of the discount rate were taken into account. The results show that machine intensive construction of PCC pavement would have the. lowest life-cycle cost of the three alternatives. In the economi analysis, only highway agency costs were included, it being tacitly assumed that vehicle operating costs, and indirect benefits, would not be significantly different irrespective of the alternative selected.